Alterations in Systemic and Cognitive Glucocorticoid Sensitivity in Depression - Gaffey, Allison E. (Biol Psychiatry Cogn Neurosci Neuroimaging, 2018)
BACKGROUND: Decades of research point to cortisol insensitivity as a biomarker of depression. Despite a vast literature on cortisol’s effects on memory, the role of cortisol insensitivity in core psychological features of depression, such as emotional memory biases, is unknown. METHODS: Sixty-five pre-menopausal women with varying levels of depression completed this study involving an at-home low-dose dexamethasone suppression test (DST) and four experimental sessions (i.e., two visits for memory encoding of emotional pictures, each of which was followed 48 hours later by a recall test). Participants received 20 mg oral cortisol (CORT) or placebo prior to encoding. We tested whether systemic cortisol insensitivity measured with the DST predicted cognitive sensitivity to CORT, which was operationalized as change in negatively biased memory formation for pictures encoded during CORT vs. placebo. RESULTS: Cortisol insensitivity was associated with more severe depression and flatter diurnal cortisol. Cortisol insensitivity predicted negative memory bias for pictures encoded during placebo and reduction in negative memory bias for pictures encoded during CORT (vs. placebo), even after accounting for psychiatric symptomatology. CONCLUSIONS: Our findings replicate research showing that cortisol insensitivity predicts depression severity and flatter diurnal cortisol. The results further suggest that systemic cortisol insensitivity is related to negative memory bias and its alleviation by acute cortisol administration. These novel cognitive findings tie together knowledge regarding endocrine and psychological dysfunction in depression, and suggest that boosting cortisol signal may be cognitively beneficial in individuals with cortisol insensitivity. TRIAL REGISTRATION: ClinicalTrials.gov: Depression, Adversity, and Stress Hormones (DASH) Study; https://clinicaltrials.gov/ct2/show/NCT03195933; NCT03195933.